U-Pb Zircon Geochronology and Nd Isotopic Signatures of the Pre-Mesozoic Metamorphic Basement of the Eastern Peruvian Andes: Growth and Provenance of a Late Neoproterozoic to Carboniferous Accretionary Orogen on the Northwest Margin of Gondwana - Cardona Molina, Agustín (2009)
This study integrates U-Pb zircon geochronology (from LAM-ICP-MS, SHRIMP, and TIMS) with Nd isotopic data from orthogneisses and metasedimentary rocks of the pre-Mesozoic basement of the eastern Peruvian Andes to provide new information on the tectonic evolution and Neoproterozoic-Paleozoic paleogeography of this segment of the protoAndean margin. A high-grade orthogneiss unit yields U-Pb zircon protolith crystallization ages of ∼613 Ma. It was metamorphosed and intruded by an Early Ordovician granitoid. Subsequently, two different volcano-sedimentary sequences were laid down and metamorphosed, probably as a consequence of terrane accretion. The older sequence was deposited and metamorphosed between 450 and 420 Ma, and the younger one was deposited after 320 Ma and metamorphosed at 310 Ma. U-Pb detrital zircon age patterns from the two sequences are within the age intervals 315–480, 480–860, 960–1400, and 11400 Ma. These data strongly suggest geological and spatial links between the different units, implying the existence of active magmatism contemporaneous with the reworking of previously formed orogenic complexes. Mesoproterozoic and older ages suggest that the detrital sources are on the western margin of Gondwana, near the Amazonian Craton and/or other Grenvillian-type domains, such as those found within the Andean belt. Neoproterozoic to Ordovician zircons suggest that this crustal segment was formed on an active margin along the western side of the Amazonian Craton. Whole-rock Nd isotope data from metasedimentary rocks of the two younger units yield Nd (450 Ma, 310 Ma) values between 6.3 and 13.2 and Sm-Nd TDM model ages between 1.6 and 2.1 Ga. The comparison of the Nd isotope record with the U-Pb detrital zircon data suggests that recycling of older crust was an important factor in the growth of the central Peruvian segment of the proto-Andean margin during the Proterozoic and the Early Paleozoic. Different tectonic and paleogeographic models are discussed in light of the new data presented here.